Glitter (Guided Literation Movement) Model Development In Junior High School - Sulistyono, Antonius Hariadi; Dwikurnaningsih, Yari (Jurnal Pendidikan Indonesia, 2020)
This research aims to describe and develop GLS SMP management at this time, its strengths and weaknesses, and the development of an effective GLS management model in SMP. This type of research is development research. Data collection methods use data triangulation (questionnaire, interview, documentation). Data were analyzed using qualitative descriptive techniques. The results of the research show: Model validation was carried out by experts with the results of the validation showing the Glitter SMP model was considered very feasible with an average score of 81.51. The model was tested on the GLS implementers of SMP Negeri 1 Bawen, Semarang Regency, Central Java with the average results of eligibility 84.09. The conclusion is that the Glitter SMP model can be applied effectively in the implementation of GLS in SMP.